Echinosporin antibiotics isolated from Amycolatopsis strain and their antifungal activity against root-rot pathogens of the Panax notoginseng - Xu, Xindong; Han, Li; Zhao, Lixing; Chen, Xiao; Miao, Cuiping; Hu, Linfang; Huang, Xueshi; Chen, Youwei; Li, Yiqing (Folia microbiologica, 2019)
Actinomycete strain YIM PH20520, isolated from the rhizosphere soil sample of Panax notoginseng collected in Wenshang, Yunnan Province, China, exhibited antifungal activity against root-rot pathogens of the Panax notoginseng. The structures of bioactive molecules, isolated from the ethyl acetate extract of the fermentation broth of the strain, were identified as echinosporin (1) and 7-deoxyechinosporin (2) based on extensive spectroscopic analyses. 1 exhibited antifungal activity against four tested root-rot pathogens of Panax notoginseng include Fusarium oxysporum, Fusarium solani, Alternaria panax, and Phoma herbarum with the MIC value at 64, 64, 32, and 64 μg/mL, respectively. 2 exhibited antifungal activities against F. oxysporum, F. solani, A. panax, and P. herbarum with the MIC value at 128, 128, 64, and 128 μg/mL, respectively. Based on the phylogenetic analyses, the closest phylogenetic relative of strain YIM PH20520 is Amycolatopsis speibonae JS72T (97.69%), so strain YIM PH20520 was identified as Amycolatopsis strain. To the best of our knowledge, this is the first report of echinosporin antibiotics isolated from Amycolatopsis strain besides Streptomyces strain and their antifungal activity against four tested root-rot pathogens of the Panax notoginseng. The results provide a reliable evidence for the following related biosynthetic investigations on Amycolatopsis strain YIM PH20520 due to echinosporins antibiotics' unique tricyclic acetal-lactone structures.
Keywords: Actinobacteria; kořeny rostlin; Plant Roots; molekulární struktura; China; RNA, Ribosomal, 16S; Antifungal Agents; Panax notoginseng; Čína; fylogeneze; Fungi; Phylogeny; Rhizosphere; rhizosféra; Microbial Sensitivity Tests; RNA ribozomální 16S; nemoci rostlin; Plant Diseases; houby; antifungální látky; mikrobiální testy citlivosti; laktony; Lactones; Molecular Structure